PENINGKATAN KUALITAS BENIH JAGUNG DENGAN PEMBERIAN KOMBINASI NITROGEN ASAL PUPUK ANORGANIK DAN ORGANIK - Endang Sri Dewi HS (Agroland: Jurnal Ilmu-ilmu Pertanian, 2012)
The need for maize continues to increase along with the population increase. However, maize production is often constrained due to the use of non quality of seed. Attempts to overcome this problem are produce high physiological quality of seed. High physiological quality of maize seed can be obtained through the efficient of nutrient management, especially nitrogen (N). Nitrogen is an essential nutrient that affects the formation of the vegetative organs of maize. Nitrogen can be obtained through the application of fertilizers, both organic and inorganic fertilizer such as cow manure and urea. This research has been carried out in order to study the effect of doses combination of nitrogen comes from cow manure and urea fertilizer for optimum growth, seed yield and seed quality of maize. The research was conducted in January-May 2012, in the greenhouse of the Faculty of Agriculture, Gadjah Mada University. The research was conducted in a single factor arranged in completely randomized design (CRD) with 5 levels of treatments, namely N0: 100% of N comes from urea (5.25 g/polybag), N1: 25% of N comes from cow manure (114 g/polybag) + 75 % of N comes from urea (3.93 g/polybag), N2: 50% of N comes from cow manure (227 g/polybag) + 50% of N comes from urea (2.62/polybag), N3: 75% of N comes from cow manure (342 g/polybag) + 25% of N comes from urea (1.31 g/polybag) and N4: 100% of N comes from cow manure (455 g/polybag). Observations were done on several variables such as physiological activity, growth, yield components, seed yield and seed quality of maize. Data were analyzed with Analysis of Variance (ANOVA) at 5% level, and continued with Duncan Multiple Range Test (DMRT). The results showed that the N2 gives the better growth, seed yield and seed quality of maize when compared to N0, N1, N3 and N4. There was a positive correlation between N uptakes by maize with seed quality produced.